FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN PADA MAMAMIA CABANG PAMULARSIH SEMARANG - Oky Chorniawan, 08.05.51.0143; Moelatsih, Moelatsih (Students Journal of Economic and Management, 2012)
Mamamia Pamularsih Branch Semarang is one of a fast-food franchise. The reason for choosing the object of the research is that Mamamia Stake and Shake franchise was experiencing problems in the business development. The problem is the imergence of other similiar franchise businesses cheaper price. Therefore it is necessary to do a research to know and to analyze the influenceof the product quality , prices and promotion towards the purchase decision of product in Mamamia Pamularsih Branch Semarang. The samples was taken from 100 respondents by using random sampling technique, in which the respondents are customers who buy product in Mamamia Pamularsih Branch Semarang, where the research is conducted. Testing the result obtained that in partial there are positive influence and significant between products purchase of the decision; in partial there are positive influence and significant between price of the decision purchase and is partial there are positive influence and significant between promotion of the decision purchase. The coefficient of determination of 0,722 it means that products, prices and promotion have contribution of 72,20 % confirms that the decision purchase.Key words : Price, Product, Promotion, Purchasing Decision.